Psikologi Pendidikan: Guru Dan Proses Mengajar-Belajar - Rohana, Etep; M, Muhammad Mirwan; Rizki, Kiki (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2024)
Teaching and learning activities are the main function and most strategic effort to realize the institutional goals carried out by the institution. In order to carry out institutional functions and duties, teachers have a position as central figures. The purpose of this research is to determine the teacher's relationship to the student teaching-learning process. In this research, we used a literature review method which summarizes writings about articles from various sources such as journals, books, magazines and other relevant documents and describes theories and information from both the past and the present. In this way, we get the result that the role of teachers in the world of modern education as it is today is increasing from just being a teacher to being a director of learning. In this way, teachers' duties and responsibilities become more complex and difficult, so that every teacher is expected to be clever in directing students' learning activities in order to achieve learning success (academic performance) as set out in the teaching-learning process (PMB) activity targets.